System Integration for Real-Time Laser Scanning Confocal Microscope - Gumus, Gokhan; Sarioglu, Baykal; Gokdel, Yigit Daghan (IEEE, 2016)
In this work, a laser scanning confocal microscopy system governed by a software controlled DAQ Card is presented. The presented system can be utilized for scanning a target and displaying the resulting image through a designed graphical user interface (GUI). The system performs two main operations: (1) generation of the actuation signal and (2) image acquisition. The architecture of the proposed system and successful operation of the system is demonstrated by constructing images from USAF51 negative resolution test target. In the experiments, the proposed system is operated at the slow scan frequency (f (s)) of 1 Hz and the fast scan frequency (f (fast)) of 100 Hz with a sampling frequency (f (fast)) of 20 kHz. The experimental results show that 1 mu m lateral resolution is achieved in the proposed system.
24th Signal Processing and Communication Application Conference (SIU) -- MAY 16-19, 2016 -- Zonguldak, TURKEY
Keywords: Laser Scanning Microscope; İmage Processing; Confocal Microscope